Spinal Anesthesia for Cesarean Delivery of a Pulmonary Arterial Hypertension Parturient; A Case Report - Mohajerani, Seyed Amir; Moosavi, Seyed Mojtaba; Aminnejad, Reza (Annals of Anesthesiology and Critical Care, 2018)
Anesthesia for parturients with pulmonary arterial hypertension (PAH) is challenging. Successful management of anesthesia in PAH parturients during labor requires an interdisciplinary approach and a multidisciplinary team. During parturition, neuraxial anesthesia can be a safe and reasonable choice in this group of patients. Choosing the safest anesthesia method is always a challenge in this scenario. In a case report study, the current researchers used management of anesthesia with neuraxial block and preserving afterload and meticulous control of pulmonary hypertension